Factors determining the transition of the agricultural sector to market relations (Economics and region, 2024)
The power of any nation or state depends largely on its political and economic development. The importance of the efficiency of the economy of an agricultural sector in ensuring the socio-economic stability of the country depends on the purposeful organisation of market relations operating in this sector of the economy and their direction in the appropriate direction. The purposeful organisation of the agricultural market means, first of all, regulating the market by economic means. In this way, the mechanism of interaction between producers and consumers of agricultural products is established in a form suitable for the country's economy. It is natural that the implementation of measures to regulate the agricultural market through economic instruments often involves state intervention. However, with the development of market relations, these instruments perform a self-regulating function. In modern conditions the regulatory policy is regulated by systematic use of price, money-credit, budget, tax, customs, insurance and other economic instruments. The state intervention in the agricultural market by means of economic regulation methods is also characterised by the fact that if the production of certain products to be put on the market does not meet the country's needs, the relationship between supply and demand is adjusted mainly at the expense of imported products. The concept of solving agrarian problems under market conditions was the subject of serious disagreement among Azerbaijani agrarian economists. Although there are different opinions about the way out of the situation in the country, the transition to market relations has become an objective necessity. Thus, after the destruction of the centralised planned economic system, after the creation of independent states, each country, including the independent state of Azerbaijan, has determined its own development path, determined the future development path and set the goal of transition to market relations. Therefore, the development of the agricultural sector, which is considered to be the leading sector of the economy, requires the correct determination of the directions and ways of transition to market relations.
Keywords: market infrastructure; agricultural market; economic mechanism; price; profit